(untitled) (American International Journal of Biology and Life Sciences, 2021)
The Purpose of the research: The study aimed to document the Asteraceae species in the study area. The study also examined the species diversity and medicinally important plants. Data, Materials, and Methodology: The work is based on fresh materials collected during thirty-six field visits to Paba Upazila of Rajshahi district, Bangladesh was carried out from November 2018 to October 2019 to cover the seasonal variations. Plant parts with either flower or fruits collected using traditional herbarium techniques to make voucher specimens for documentation. The results: The result shows in all, 44 species under 35 genera of the family Asteraceae were reported, out of which 40 (90.90%) were used medicinal applications for the treatment of more than 59 diseases. Major findings: The findings of the study that 25% of species were very common, 43.18% were common, 25% species were rare and 6.82% species were very rare in the study area. Mikania cordata (Burm.f.) Robinson is the only climbing species. Blumea laciniata (Roxb.) DC. and Wedelia trilobata (L.) Hitchc. has been reported for the first time in Paba Upazila of Rajshahi. The present study will help in identifying the major Asteraceae species for further investigation and also beneficial to develop the herbal drug development.